2017
DOI: 10.1002/adhm.201700192
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Liquid Marbles for Biomedical Applications: A Critical Review

Abstract: Liquid marbles (LM) are freestanding droplets covered by micro/nanoparticles with hydrophobic/hydrophilic properties, which can be manipulated as a soft solid. The phenomenon that generates these soft structures is regarded as a different method to generate a superhydrophobic behavior in the liquid/solid interface without modifying the surface. Several applications for the LM have been reported in very different fields, however the developments for biomedical applications are very recent. At first, the LM prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 130 publications
(330 reference statements)
1
67
0
Order By: Relevance
“…Recently, researchers have applied the LM to culture cells in the 3D format by manually rolling the medium on a hydrophobic powder. [35][36][37][38][39] However, the proposed method applied a tedious manual culture process and the sustained supply of nutrients and medium during medium renewal was difficult to achieve, [40] which hampered the long-time culture of the 3D cell spheroid.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have applied the LM to culture cells in the 3D format by manually rolling the medium on a hydrophobic powder. [35][36][37][38][39] However, the proposed method applied a tedious manual culture process and the sustained supply of nutrients and medium during medium renewal was difficult to achieve, [40] which hampered the long-time culture of the 3D cell spheroid.…”
Section: Introductionmentioning
confidence: 99%
“…These systems exhibit novel characteristics such as low coefficients of friction [13,14,15], which have been exploited by nature [16,17]. It has been demonstrated that liquid marbles have myriad uses ranging from micro-bioreactors [18,12,19,20] to gas biosensors [21,22] to unconventional computing media [23,24]. Our laboratory has developed LM devices that are capable of implementing computation through a variety of non-standard logics [23,24,25] where the LMs are considered as data or otherwise, to contain data (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid marble (LM), a self‐standing micro‐scale aqueous droplet coated with a hydrophobic material, has attracted considerable attention in biotechnological applications . Shen et al first demonstrated a blood‐typing system by generating a blood marble as a micro‐bioreactor .…”
Section: Introductionmentioning
confidence: 99%
“…[7] Liquid marble (LM), [8] a self-standing micro-scale aqueous droplet coated with a hydrophobic material, has attracted considerable attention in biotechnological applications. [9] Shen et al first demonstrated a blood-typing system by generating a blood marble as a micro-bioreactor. [10] The successful cultivation of microorganisms in LM [11] yielded cellular spheroids [12] and further the construction of a toroidal tissue structure [13] by spatially organizing LMs.…”
Section: Introductionmentioning
confidence: 99%